Research on the Evaluation of the Efficiency of Production Processes Through the Implementation of Key Performance Indicators - Sujová Erika; Vysloužilová Daniela; Koleda Peter; Gajdzik Bożena (Management Systems in Production Engineering, 2023)
The paper deals with the implementation of key performance indicators (KPI) for the evaluation of the efficiency of production processes. A key performance indicator is a measurable indicator that expresses how effectively the company achieves key goals in both production and non-production areas. As part of the research, various process key performance indicators characterizing product quality were identified. The indicator of the number of faulty products in relation to the volume of production (EXTppm) was chosen for the research. The monthly development of EXTppm in the course of 2022 and the long-term development in the years 2012-2022 were evaluated. The research was also devoted to the analysis of the reasons for not achieving the KPI target values, and measures were proposed to eliminate poor quality, respectively reduction of the number of complained products.